2011
DOI: 10.1038/hr.2010.281
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic receptor gene polymorphism is a genetic risk factor for cardiovascular disease: a cohort study with hypertensive patients

Abstract: Single-nucleotide polymorphisms (SNPs) of the b-adrenergic receptor (bADR) subtypes are related to hypertension and obesity. This hospital-based cohort study with hypertensive patients evaluated five bADR SNPs in association with cardiovascular events. The cohort included 357 hypertensive patients (male¼181; mean age¼61.5 ± 11.8 years) seen between January 1998 and June 2004. The SNPs (Ser49Gly and Arg389Gly for b 1 ADR; Gly16Arg and Glu27Gln for b 2 ADR; Trp64Arg for b 3 ADR) were identified by PCR. We used K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…Some clinical studies pointed on possible relationship between AH and Trp64Arg polymorphism [17,35,36], as well as relationship between this genotype and higher mortality among hypertensives [37]. In our study, we found an association of Trp64Arg carrier state with AH (p < 0.019).…”
Section: Discussionsupporting
confidence: 65%
“…Some clinical studies pointed on possible relationship between AH and Trp64Arg polymorphism [17,35,36], as well as relationship between this genotype and higher mortality among hypertensives [37]. In our study, we found an association of Trp64Arg carrier state with AH (p < 0.019).…”
Section: Discussionsupporting
confidence: 65%
“…21 Cohort studies have shown rs4994 to be a genetic risk factor for cardiovascular disease in hypertensive patients. 22 However, the effect of rs4994 remains unclear. 23 Studies performed on Chinese Han individuals remain rare.…”
Section: Discussionmentioning
confidence: 99%
“…These functions render 2 -AR an important target for cardiovascular disease (CVD) therapy [15,22,23]. Interestingly, studies reported 2 -AR dysfunction to be implicated in the pathogenesis of several CVD including hypertension [24][25][26][27], coronary heart disease [13,23], idiopathic dilated cardiomyopathy [28], congestive heart failure [29,30], idiopathic ventricular arrhythmias [31], and sudden cardiac death [32].…”
Section: Introductionmentioning
confidence: 99%